Test data distribution system for OSS/BSS-systems testing - Nikolaev Steven; Sitnikov Igor (ITM Web of Conferences, 2019)
OSS/BSS-systems used by telecommunication companies to conduct their business are a combination of several subsystems that closely interact with each other. Since the activities of telecommunications companies are related to the processing of personal data of individuals and legal entities, such systems should be subjected to testing, which should continue until the end of the life cycle. The huge size of telecommunications companies' databases, as well as the number of tests required to cover the entire functionality of OSS/BSS-systems are an obstacle to conducting rapid testing. This article describes an approach to testing organization that solves this problem, based on the selection and keeping the test data up to date. The effectiveness of the proposed approach has been demonstrated experimentally.